Estudo da oxidação de AlAs em heteroestruturas semicondutoras - Mcglennon da Rocha Regis (2002)
In this work, we investigate the oxidation processing of AlAs in semiconductor AlAs/GaAs multilayer structures. Our results show a direct dependence of the depth of oxidation with the time of exposure to the oxidating atmosphere. This leads to a change in the reflectivity of the multilayer structures, shifting the reflectivity maximum range towardslower wavelengths. We could demonstrate the loss of As in the oxidized regions. In our samples we could also observe a deepning of the oxidated regions relative to the non-oxidated ones. We conclude that the oxidation process takes place more significantly in the AlAs layer, in comparison with the GaAs ones.